ELECTRONIC POCKET BOOK ABOUT ARTOCARPUS DIVERSITY ON THE RIVER BANKS, BERINGIN KENCANA VILLAGE, TABUNGANEN, NORTH BARITO - Rida Sita Dewi; Hardiansyah Hardiansyah; Mahrudin Mahrudin (Universitas Negeri Padang, 2022)
Indonesia has an abundance of Artocarpus species. The genus Artocarpus has 30 species spread across Indonesia. This research is a type of development with research results oriented to field data which is then made into a product in the form of an HTML 5-based electronic pocket book enrichment material that will be used for high school students. HTML 5 based electronic pocket book, which is about the diversity of Artocarpus species on the riverbanks of Beringin Kencana Village, Tabunganen District which is compiled as enrichment material. The research method is research and development (R&D) with the Borg and Gall model. The results showed as many as 6 types of Artocarpus namely Nangka (Artocarpus heterophyllus Lamk.), Nangka Bilulang (Artocarpus heterophyllus Lamk.), Nangka Bubur (Artocarpus heterophyllus Lamk.) which was included in one variety, Sukun (Artocarpus altilis (Park.) Fosberg.), Cempedak (Artocarpus integer (Thunb.) Merr.) and Keledang (Artocarpus lanceifolius Roxb.) are other species. The electronic pocket book that was developed obtained the criteria of